153k views
19 votes
Hello! Will someone please help me with expanding and simplifying this?:

3(m+2) + 4(6+m)

1 Answer

9 votes

Answer: 7m+30

=============================================

Work Shown:

3(m+2) + 4(6+m)

3m+6 + 24 + 4m

(3m+4m) + (6+24)

7m+30

------------

Step-by-step explanation:

In the second step, I used the distribution rule a*(b+c) = a*b+a*c. We multiply the outer term by every term inside. So for instance 3(m+2) = 3*m+3*2 = 3m+6. A similar situation applies to 4(6+m) as well. Afterward, I grouped and combined like terms.

We can think of 3m+4m = 7m as saying "I have 3 maps and someone gave me 4 more maps, so that means I have 3+4 = 7 maps now". The m is a place holder for any number.

User Bcholmes
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.